PERIOD VARIATIONS IN THE CLOSE BINARY BM UMa - Virnina, N. A.; Panko, E. A.; Sergienko, O. G.; Murnikov, B. A.; Gubin, E. G.; Klabukova, A. V.; Movchan, A. I. (Одеські астрономічні публікації, 2010)
We present the results of analysing of the light curve and O–C variations in the eclipsing system BM UMa, based on V-band observations which cover the period from JD 2454933 to 2454961 using two robotic remotely-controlled telescopes of Tzec Maun Observatory (USA) along with observations made with the RK-600 telescope of Odessa Astronomical Observatory. The full light curve displays a total primary eclipse with a duration 0.06 of the period, or 24 minutes, and a partial secondary eclipse, with both maxima of equal magnitude. For our obesrvations, we determined the statistically optimal values of the initial epoch of T0 = 2454944.2814 ± 0.0001 and orbital period of P = 0.d271226± 0.000002. The depths of primary and secondary minima are nearly equal, 0.m838 ± 0.006 and 0.m748 ± 0.006, respectively. The physical parameters of the system were calculated using the Wilson-Devinney code, appended with the Monte Carlo search algorithm. The result establishes BM UMa as a contact system (fillout factor 10.7%) with parameters: mass ratio 0.538 ± 0.001, inclination 86.°815 ± 0.005, and temperatures of components 4700 ± 20 K and 4510 ± 10 K. The more massive component is larger and cooler. The 72 archival and 11 newly-obtained times of light minimum cover the interval 1961-2010 and allowed us to exclude possible systematic period variations in BM UMa and to determine an initial epoch of HJD 2447927.382 and orbital period of P = 0.d2712209± 0.0000006.